Enhancing Trust, Transparency and Accountability in The Local Development Process - Woro, Sri Juni; Supriyanto, Supriyanto (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
Research indicates that accountability system has not been effectively implemented yet and the pattern is found out to be bureaucratic. In order to revitalize this system, we should emphasize and pay more attention on: (1) the improvement of capacity in strategic planning formulation process, and (2) the effectiveness of performance monitoring and evaluation. To accelerate both, the support of proper Information Communication Technologies (ICTs) and e-Government system is of vital importance. This research result, that revitalization for accountability system that emphasizes the need to establish a new functional institutions, namely GAPURA KOTA model.